2016
DOI: 10.1111/irv.12429
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐sectional survey and surveillance for influenza viruses and MERS‐CoV among Egyptian pilgrims returning from Hajj during 2012‐2015

Abstract: BackgroundApproximately 80 000 Egyptians participate in Hajj pilgrimage annually. The purpose of this study was to estimate influenza virus and MERS‐CoV prevalence among Egyptian pilgrims returning from Hajj.StudyA cross‐sectional survey among 3 364 returning Egyptian pilgrims from 2012 to 2015 was conducted. Nasopharyngeal (NP) and oropharyngeal (OP) swabs were collected from all participants. Sputum specimens were collected from participants with respiratory symptoms and productive cough at the time of their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
47
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 12 publications
5
47
1
Order By: Relevance
“…However, the vaccination uptake was better than that of some other Arab countries. For instance, pilgrims from Egypt had a vaccination coverage of 9%, 30% and 19% during 2013-2015 respectively [32]. These findings concur with data from a recent vaccine coverage survey in the Gulf Cooperation Council (GGC) countries, showing an influenza vaccination rate of 15% to 24% [45], indicating the need for enhancing vaccination uptake among pilgrims from Arab countries.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…However, the vaccination uptake was better than that of some other Arab countries. For instance, pilgrims from Egypt had a vaccination coverage of 9%, 30% and 19% during 2013-2015 respectively [32]. These findings concur with data from a recent vaccine coverage survey in the Gulf Cooperation Council (GGC) countries, showing an influenza vaccination rate of 15% to 24% [45], indicating the need for enhancing vaccination uptake among pilgrims from Arab countries.…”
Section: Discussionsupporting
confidence: 78%
“…Several studies measuring influenza vaccination rate among French pilgrims revealed vaccine uptake that fluctuated generally between 26% and 46% over the years 2006 to 2013, with extremes of up to 97% in 2009 and zero in 2013 (due to unavailability of vaccine before Hajj) [27][28][29][30][31]. A large study among Egyptian pilgrims (who represent about 4% of the total pilgrims) revealed low influenza vaccination rates of between 9% and 30% in the years 2012 to 2015 [32].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in the United States the 2014-2015 season was predominated by pandemic H1N1 and H3N2 was more common during the 2016-2017 season [34,35].We found that influenza rather than MERS-CoV was more common among the tested patients. The findings are also consistent with other studies among travelers and pilgrims where influenza far exceeded MERS [36][37][38][39][40]. Similarly, in a small study in Saudi Arabia, influenza viruses were detected in 16% of 182 patients [29].…”
Section: Discussionsupporting
confidence: 91%
“…Since 2012, event-based surveillance among pilgrims returning from Hajj, Umrah and other religious events in KSA has been conducted by KSA and countries sending pilgrims. While many return reporting respiratory symptoms, no MERS-CoV infections have been identified among returning pilgrims (Muraduzzaman et al, 2018;Barasheed et al, 2014;Atabani et al, 2016;Koul et al, 2017;Annan et al, 2015;Ma et al, 2017;Memish et al, 2014aMemish et al, , 2014bRefaey et al, 2017;Al-Abdallat et al, 2017;Matthew et al, 2015;Alqahtani et al, 2016;Win et al, 2016;Yavarian et al, 2018;Kapoor et al, 2014).…”
Section: Findings From the Global Technical Meetingmentioning
confidence: 99%